The Utility of Including the Strengths of Underage Drinking Laws in Determining Their Effect on Outcomes. (4th July 2015) - Fell, James C.; Scherer, Michael; Voas, Robert
<x xml:space="preserve">Abstract</x> Background To control underage drinking in the United States, which has been associated with an estimated 5, 000 deaths and 2.6 million injuries or other harm annually, each state has developed a unique set of laws. Previous research examining these laws' effectiveness has frequently focused on the laws' existence without considering variance in sanctions, enforcement, or exemptions. Methods We scored 20 minimum legal drinking age 21 (MLDA‐21) laws for their strengths and weaknesses based on (i) sanctions for violating the law, (ii) exceptions or exemptions affecting application, and (iii) provisions affecting the law or enforcement. We then replicated a 2009 study of the effects of 6 MLDA‐21 laws in 3 different ways (using identical structural equation modeling): Study 1—8 additional years of data, no law strengths; Study 2—years from the original study, added law strengths; Study 3—additional years, law strengths, serving as an update of the 6 laws' effects. Results In all 3 studies—and the original study—keg registration laws were associated with both an unexpected significant increase (+11%, p < 0.001) in underage drinking‐driver ratios and a notable 25% reduction in per capita beer consumption—opposing results that are difficult to explain. In Study 3, possession and purchase laws were associated with a significant decrease in underage drinking‐driver fatal crash ratios (−4.9%, p < 0.001; −3.6%, p < 0.001, respectively). Similarly, zero tolerance and use and lose laws were associated with reductions in underage drinking‐driver ratios (−2.8%, p < 0.001; −5.3%, p < 0.001, respectively). Conclusions Including strengths and weaknesses of underage drinking laws is important when examining their effects on various outcomes as the model fit statistics indicated. We suggest that this will result in more accurate and more reliable estimates of the impact of the laws on various outcome measures.